Thrombotic and bleeding complications in patients with AL amyloidosis - Fotiou, Despina; Theodorakakou, Foteini; Spiliopoulou, Sotiria; Gavriatopoulou, Maria; Migkou, Magdalini; Kanellias, Nikolaos; Eleutherakis‐Papaiakovou, Evangelos; Malandrakis, Panagiotis; Dialoupi, Ioanna; Roussou, Maria; Ntanasis‐Stathopoulos, Ioannis; Terpos, Evangelos; et al. (British journal of haematology, 2024)
Haemostatic abnormalities and deregulated coagulation are common complications in AL amyloidosis. The relevant risks of thromboembolic and haemorrhagic events have not been thoroughly evaluated. To describe clinically significant thrombotic/haemorrhagic events in 450 consecutive patients with AL amyloidosis. Venous thromboembolic events (VTEs) were reported in 6% and arterial embolic events (AEEs) in 5% of patients, respectively, during a 55‐month median follow‐up. Lower albumin, lower eGFR, higher BM infiltration, soft tissue involvement, IMiD‐based therapy and prior thrombosis were associated with VTE risk. Prior thrombosis was the only independent prognostic variable (HR 9.3, p = 0.001). Coronary arterial disease, prior AEE, 24‐h proteinuria and higher platelet counts were associated with AEE risk. Significant bleeding events were reported in 9%, and associated mortality was 19%. Liver involvement, higher serum creatinine and higher baseline VWF:Ag levels were linked to bleeding risk. Using competing risk analysis, the cumulative probability of thrombosis/bleeding was higher during the first year following diagnosis, but a stable lower risk for both events remained for the duration of follow‐up. In AL amyloidosis patients, the risk of thrombotic/arterial embolic events is significant, but the bleeding risk is also high. A multiparametric assessment is required to initiate anti‐thrombotic or anti‐platelet therapy appropriately.